Between Res and Verba: The Use of Myth in Francesco Patrizi's Dialoghi della retorica (Venice, 1562) - Puliafito, Ana Laura (Analysis. Journal of Philosophical Research, 2018)
This paper analyses the role played by myths in Francesco Patrizi’s Dialoghi della retorica (1562). In the discussion of the tenets of classical rhetoric contained in the work, Patrizi aims to define both the matter and the form of the discipline through the analysis of the nature of language and the limits of human knowledge. Patrizi uses some stories where fiction and history are intertwined to provide a mythical explanation of the causes behind the first decay of human social, political and intellectual life. Therefore, the present contribution will focus on Patrizi’s approach to reforming language in its rhetorical dimension, and will determine what role is reserved for fiction in the Dialogues on Rhetoric. In other words, I will try to respond with Patrizi to the following question: What meaning can fiction offer when language is employed as a way of accessing truth? Keywords: Francesco Patrizi da Cherso, Rhetoric, Aristotle, Myth and History.